Association of COX-2 Promoter Polymorphism with Gastroesophageal Reflux Disease (GERD) and Gastrointestinal Cancers from Iran: An Application for the Design of Early Detection of Cancer and Providing Prognostic Information to Patients in a Clinical Settin - Biramijamal, Firouzeh (IntechOpen, 2012)
None